2014
DOI: 10.56431/p-o2e232
|View full text |Cite
|
Sign up to set email alerts
|

Control of Rots and Spoilage of Agricultural Products: A Review

Abstract: The most important losses in agricultural production which involve the greatest costs on the farm economy occur postharvest. It is estimated that worldwide between 10 and 40% losses of agricultural produce occur postharvest. Losses are more severe in developing than developed nations of the world. Several species of fungi and in some cases bacteria participate in postharvest deterioration and rots of tubers and agro- produce. These include species of Aspergillus, Fusarium, Colletotrichum, Macrophomina, Penicil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…As a plant growth-promoting rhizobacteria (PGPR), Rhodopseudomonas palustris in Rhodopseudomonas has been studied frequently; it can utilize a variety of substances as carbon and energy sources owing to its surprising metabolic versatility, suggesting that R. palustris could be used as a beneficial inoculant in agriculture [31]. Among the affected fungi, studies have found that Penicillium and Colletotrichum participate in the postharvest deterioration and rotting of tubers [32]. PGPR is a biocompatible approach involving inoculation, which can be used to decrease negative environmental impacts, especially in soils with continued use of chemical fertilizers.…”
Section: Effects Of Straw Addition On Soil Microbial Communitiesmentioning
confidence: 99%
“…As a plant growth-promoting rhizobacteria (PGPR), Rhodopseudomonas palustris in Rhodopseudomonas has been studied frequently; it can utilize a variety of substances as carbon and energy sources owing to its surprising metabolic versatility, suggesting that R. palustris could be used as a beneficial inoculant in agriculture [31]. Among the affected fungi, studies have found that Penicillium and Colletotrichum participate in the postharvest deterioration and rotting of tubers [32]. PGPR is a biocompatible approach involving inoculation, which can be used to decrease negative environmental impacts, especially in soils with continued use of chemical fertilizers.…”
Section: Effects Of Straw Addition On Soil Microbial Communitiesmentioning
confidence: 99%
“…However, the in uence of harmful bacteria on food is considered the most serious because they spoil food and cause health effects on consumers. Globally, postharvest losses of agricultural products caused by microorganisms are estimated to range from 10 to 40% (Deshi et al, 2014;Gustavsson et al, 2011;Makavana et al, 2018;Sriram et al, 2023;Taye et al, 2023). Additionally, foodborne illnesses are prevalent around the world.…”
Section: Introductionmentioning
confidence: 99%